Effect of curcumin in prevention of pre-invasive lesions of the cervix - Rashi, .; Shaheen, .; Sharma, Rajyashri; B., Deepti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the leading cause of deaths of women due to malignancies in developing countries world-wide. Having a latency period of upto10 years, pre-invasive lesions of cervix give us a wide margin for detection and treatment before it becomes cancerous. It has been estimated that even after putting in all the resources it’s not possible to screen one fourth of the population of women in India. This is the aim of this study to establish a pattern of prevalence of these pre-invasive lesions and find out correlation with various epidemiological factors and establish best screening modality in low resourse settings like ours. Curcuminoids are the extract of curcuma longa, and it has been found to have myriad effects like anti-inflammatory, antibiotic, and anti-cancerous as well. In this study we have tried to determine its effect on precancerous lesions of the cervix. Methods: In this study, patients coming to the OPD of the Gynaecology Department with various complaints like vaginal discharge and post coital bleeding etc were subjected to en VIA examination (visual inpection with acetic acid), and cytology. Selected cases were subjected to colposcopy and biopsy, which is taken as gold standard in the study. The cases were studied in terms of their epidemiologic charecterestics. The diagnostic accuracy of VIA and cytology was assessed using colposcopy and biopsy as the gold standard, chi square test applied and power of the screening test calculated. Results: 226 cases were subjected to VIA examination, using freshly prepared 5% acetic acid .105(46.5%) cases were VIA positive. Same no of cases were also subjected to cytological evaluation. Upon cytological evaluation, 21(9.3%) had a normal cytology, 158(69.9%) were inflammatory, 3(1.3%) had ASCUS, 1(0.4%) had AGUS, 26(11.6%) had LSIL and koilocytic changes, 11(4.9%) had HSIL, and 6 cases (2.6%) had squamous cell carcinoma. Abnormal cytology (47/226) was mostly found in age group 30-40 29/47 (61.7%), were para 2 to 4 34/47 (72.3%), belonged to class IV-V socioeconomic class 28(59.6%), belonged to rural areas 32/47(68%) were illiterate 29/47(61.7%) were married at a young age 15-17 23/47(49%) and were not using any contraception 22/47(46.8%). Conclusions: Cervical cancer being one of the most easily preventable cancer owing to the easy accessibility of the cervix to the clinician, and easy screening methods available, is amenable to eradication of the disease one day.